Penerapan Kuis Berbasis Teknologi dalam Pembelajaran sebagai Bentuk Evaluasi Pembelajaran - Astiza; Nurhaedah, Siti; Kaninta, Novianti (Mataram University, 2025)
This study was motivated by the researcher’s observation that students in Class IIIB enjoy participating in quizzes at the end of learning sessions. Initially, these quizzes were conducted manually during mathematics lessons, where students would line up and be asked questions individually. The quiz served as an evaluation tool for the learning process carried out by the teacher. However, such a method proved less suitable for Indonesian language learning due to the distinct characteristics of the subject matter. Therefore, this research aimed to develop a quiz that accommodates these characteristics while integrating technology to make learning more engaging, meaningful, and effective through the use of the Wordwall website. This study employed Classroom Action Research (CAR) conducted in two cycles, using observation and evaluation scores as data collection instruments. The results indicated that the use of the Wordwall website significantly improved student learning outcomes in each cycle. In the pre-cycle phase, without using Wordwall, the students’ learning achievement was only 31%. In Cycle I, after implementing Wordwall, it increased to 63%, and in Cycle II, it further rose to 94%. These findings demonstrate that the Wordwall website is highly suitable for Indonesian language learning, which involves complex material characteristics, and is proven to enhance students’ learning outcomes while fostering greater engagement and participation in the learning process.